The original Stonehenge? A dismantled stone circle in the Preseli Hills of west Wales. (February 2021) - Pearson, Mike Parker; Pollard, Josh; Richards, Colin; Welham, Kate; Kinnaird, Timothy; Shaw, Dave; Simmons, Ellen; Stanford, Adam; Bevins, Richard; Ixer, Rob; Ruggles, Clive; Rylatt, Jim; et al.
Abstract: Abstract : The discovery of a dismantled stone circle—close to Stonehenge's bluestone quarries in west Wales—raises the possibility that a 900-year-old legend about Stonehenge being built from an earlier stone circle contains a grain of truth. Radiocarbon and OSL dating of Waun Mawn indicate construction c . 3000 BC, shortly before the initial construction of Stonehenge. The identical diameters of Waun Mawn and the enclosing ditch of Stonehenge, and their orientations on the midsummer solstice sunrise, suggest that at least part of the Waun Mawn circle was brought from west Wales to Salisbury Plain. This interpretation complements recent isotope work that supports a hypothesis of migration of both people and animals from Wales to Stonehenge.